S34 The adhesion receptor CADM1 on mast cells mediates adhesion to lung fibroblasts and smooth muscle. (2nd December 2011) - Moiseeva, E P; Roach, K; Leyland, M L; Bradding, P
Abstract : Introduction and Objectives: Cell adhesion molecule 1 (CADM1) contributes to cell–cell adhesion, viability and adhesion-induced degranulation in mast cells. We found that it is expressed as three alternatively spliced isoforms (major SP4, SP1 and minor SP6) in human lung mast cells (HLMCs). Here we investigated the role of CADM1 isoforms in the adhesion of mast cells to primary airway smooth muscle cells (ASM) and lung fibroblasts (LF). Methods: Modulation of CADM1 expression was investigated in transient transfection or adenoviral delivery in the mast cell line HMC-1 and HLMCs. Cells with overexpressed CADM1 isoforms or downregulated CADM1 were examined in cell adhesion assays. Results: CADM1 RNA interference in HMC-1 resulted in 60% reduction of surface CADM1 and complete loss of CADM1 determined by FACS and Western blotting, respectively, 6 days after transduction. This decrease in CADM1 expression reduced adhesion of transduced HMC-1 cells to ASM and LF by 42% and 50%, respectively. Downregulation of CADM1 in HLMCs reduced adhesion to ASM by 39%. HMC-1 cells transfected with SP1 (exon 8/9/11) and SP6 (exon 8/9/10/11) showed lower adhesion to LF compared to cells transfected with SP4 (exon 8/11). No differences in adhesion to ASM were found. When SP4 and SP1 isoforms were overexpressed up to 206% and 148% on the cell surface 6 days post transduction by viral delivery, this CADM1 overexpression did not change adhesion to ASM. However, increased levels of SP4 isoform increased mast cell adhesion to LF by 37%. Thus, CADM1 isoforms affected adhesion to LF differently. The CADM1 counter-receptors, examined by Western blotting, are nectin-3 on ASM and CADM1+nectin-3 on LF. Conclusions: CADM1 contributes significantly to mast cell adhesion to ASM and LF. Mast cell adhesion to ASM is likely to be limited by the number of counter-receptors on ASM. In contrast, mast cell adhesion to LF is determined by the levels of SP4 isoform on mast cells. Increased levels of other CADM1 isoforms do not increase adhesion to LF. It is likely that increased levels of longer SP1 and SP6 isoforms in proportion to the CADM1 pool decrease mast cell adhesion to LF.